ANALISIS PERBANDINGAN KINERJA REKSADANA SYARIAH TERHADAP REKSADANA KONVENSIONAL (REKSADANA MAWAR) TAHUN 1997 – 2001 - Sofyan S Harahap (Universitas Trisakti, 2003)
As one type of investment porfollos, the paper discusses the comperative of financial perfor- mance of syariah mutual fund and conventional mutual fund.Acase study, descriptive method is used as research method, it isexpected to describe about the character of syariah mutual fund and conventional mutual fund. Research was conducted from January 1. 1998 to De- cember 31, 2001. Syariah Investment fund is compared to Danareksa mawar (conventional) under one investment management by PT. Danareksa Investment Management. Perfor- mance evaluation was based on: Direct comparative method, Sharpe method, Treynor and Jensen method. The paper shows that đuring 1998-2001 the financial performance of